'Dominating-set-based' searching in peer-to-peer networks. (3rd January 2006) - Yang, Chunlin; Li, Xiuqi
The 'peer-to-peer' network for sharing information and data through direct exchange has emerged rapidly in recent years. The searching problem is a basic issue that addresses the question 'Where is X?'. In this paper, we propose a 'dominating-set-based', 'peer-to-peer' searching algorithm to maximise the return of searching results while keeping a low cost for both searching and creating/maintaining the 'connected dominating set' (CDS) of the 'peer to peer' network. This approach is based on random walk. However, the searching space is restricted to dominating nodes. Simulation has been done and results are compared with the one using regular random walk.